2017
DOI: 10.3390/computation5030035
|View full text |Cite
|
Sign up to set email alerts
|

Using an Interactive Lattice Boltzmann Solver in Fluid Mechanics Instruction

Abstract: Abstract:This article gives an overview of the diverse range of teaching applications that can be realized using an interactive lattice Boltzmann simulation tool in fluid mechanics instruction and outreach. In an inquiry-based learning framework, examples are given of learning scenarios that address instruction on scientific results, scientific methods or the scientific process at varying levels of student activity, from consuming to applying to researching. Interactive live demonstrations on portable hardware… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Glessmer et al assessed the efficacy of lowaccuracy real-time CFD simulations to teach the basics of fluid mechanics. Results showed that both students' interest and comprehension on the topic were increased with using real-time CFD in an active learning environment (Glessmer and Janßen, 2017). The fundamental goal of the present research is to scrutinize the system design process of AV/VR with interactive multiphysics CFD simulations.…”
Section: Utilization Of Cfd Simulations In Educationmentioning
confidence: 91%
“…Glessmer et al assessed the efficacy of lowaccuracy real-time CFD simulations to teach the basics of fluid mechanics. Results showed that both students' interest and comprehension on the topic were increased with using real-time CFD in an active learning environment (Glessmer and Janßen, 2017). The fundamental goal of the present research is to scrutinize the system design process of AV/VR with interactive multiphysics CFD simulations.…”
Section: Utilization Of Cfd Simulations In Educationmentioning
confidence: 91%